Rapsyn facilitates recovery from desensitization in fetal and adult acetylcholine receptors expressed in a muscle cell line. (17th June 2019) - Cetin, Hakan; Liu, Wei; Cheung, Jonathan; Cossins, Judith; Vanhaesebrouck, An; Maxwell, Susan; Vincent, Angela; Beeson, David; Webster, Richard
Abstract : Key points: The physiological significance of the developmental switch from fetal to adult acetylcholine receptors in muscle (AChRs) and the functional impact of AChR clustering by rapsyn are not well studied. Using patch clamp experiments, we show that recovery from desensitization is faster in the adult AChR isoform. Recovery from desensitization is determined by the AChR isoform‐specific cytoplasmic M3–M4 domain. The co‐expression of rapsyn in muscle cells induced AChR clustering and facilitated recovery from desensitization in both fetal and adult AChRs. In fetal AChRs, facilitation of recovery kinetics by rapsyn was independent of AChR clustering. These effects could be crucial adaptations to motor neuron firing rates, which, in rodents, have been shown to increase around the time of birth when AChRs cluster at the developing neuromuscular junctions. Abstract: The neuromuscular junction (NMJ) is the site of a number of autoimmune and genetic disorders, many involving the muscle‐type nicotinic acetylcholine receptor (AChR), although there are aspects of normal NMJ development and function that need to be better understood. In particular, there are still questions regarding the implications of the developmental switch from fetal to adult AChRs, as well as how their functions might be modified by rapsyn that clusters the AChRs. Desensitization of human muscle AChRs was investigated using the patch clamp technique to measure whole‐cell currents in muscle‐type (TE671/CN21) and non‐muscle (HEK293) cell lines expressing either fetal or adult AChRs. Desensitization time constants were similar with both AChR isoforms but recovery time constants were shorter in cells expressing adult compared to fetal AChRs ( P  < 0.0001). Chimeric experiments showed that recovery from desensitization was determined by the M3–M4 cytoplasmic loops of the γ‐ and ε‐subunits. Expression of rapsyn in TE671/CN21 cells induced AChR aggregation and also, surprisingly, shortened recovery time constants in both fetal and adult AChRs. However, this was not dependent on clustering because rapsyn also facilitated recovery from desensitization in HEK293 cells expressing a δ‐R375H AChR mutant that did not form clusters in C2C12 myotubes. Thus, rapsyn interactions with AChRs lead not only to clustering, but also to a clustering independent faster recovery from desensitization. Both effects of rapsyn could be a necessary adjustment to the motor neuron firing rates that increase around the time of birth. Key points: The physiological significance of the developmental switch from fetal to adult acetylcholine receptors in muscle (AChRs) and the functional impact of AChR clustering by rapsyn are not well studied. Using patch clamp experiments, we show that recovery from desensitization is faster in the adult AChR isoform. Recovery from desensitization is determined by the AChR isoform‐specific cytoplasmic M3–M4 domain. The co‐expression of rapsyn in muscle cells induced AChR clustering and facilitated recovery from desensitization in both fetal and adult AChRs. In fetal AChRs, facilitation of recovery kinetics by rapsyn was independent of AChR clustering. These effects could be crucial adaptations to motor neuron firing rates, which, in rodents, have been shown to increase around the time of birth when AChRs cluster at the developing neuromuscular junctions.